Structural, Optical, and Antimicrobial Characterization of Cr2O3 Nanoparticles Prepared by Pulsed Laser Ablation - Mawat, M.M.; Mohamed, A.N.; Razaq, M. Kh.; Odah, J. F. (Physics and Chemistry of Solid State, 2026)
This study shows the preparation of chromium oxide (Cr2O3) nanoparticles (NPs) by pulsed laser ablation in liquid (PLAL), a simple and cost-effective method for producing high-purity nanomaterials. The structural properties of chromium oxide were examined using X-ray diffraction (XRD) and the results showed that the formation of pure eskolaite-phase Cr2O3 with a rhombohedral crystal structure and SEM analysis revealed lower laser energies (300–400 mJ) tends to produce smaller, well-dispersed particles, as the energy is sufficient for ablation but not excessive to cause extensive particle fusion, while higher laser energies (500–600 mJ) result in larger particles with increased aggregation, likely due to higher thermal input, enhanced diffusion, and re-nucleation of NPs in the liquid medium while, Optical analysis revealed a slight band gap increase with higher laser energy, attributed to the Burstein-Moss shift, where the Fermi level moves into the conduction band, altering electronic transitions. The nanoparticles demonstrated pronounced antibacterial activity against Klebsiella pneumoniae, Escherichia coli, and Staphylococcus epidermidis. Conversely, their antimicrobial effect was notably diminished against Candida albicans and Staphylococcus aureus, suggesting a differential interaction between the Cr2O3 NPs and the cellular structures of these microorganisms. This variation in antimicrobial activity underscores the potential of Cr2O3 NPs in targeted antibacterial applications.